2019
DOI: 10.1177/0018726719859404
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s not all it’s cracked up to be’: Narratives of promotions in elite professional careers

Abstract: How do organizational decision-makers and promotion candidates experience promotions in elite professional careers? Despite literature recognizing that promotions are important career events for organizations and individuals, this question has received little scholarly attention.Drawing on a narrative approach and combining spoken and visual accounts, this article examines how organizational decision-makers and promotion candidates experience the promotion to partnership in law firms. Our study reveals four na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…The paper thus adds theoretical grounding to studies that have highlighted the role of landscapes in providing moral context for narratives (e.g. Clifton, 2018; Whittle and Mueller, 2011), or the capacity of individuals to personally interpret organisational discourses (Gustafsson and Swart, 2020; Pérez and Sabelis, 2019), and complements studies which have focused on the role of individuals in co-constructing shared versions of the organisation through collective stories and narrative identities (Foroughi, 2020; Savage et al, 2018; Sörgärde, 2020).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The paper thus adds theoretical grounding to studies that have highlighted the role of landscapes in providing moral context for narratives (e.g. Clifton, 2018; Whittle and Mueller, 2011), or the capacity of individuals to personally interpret organisational discourses (Gustafsson and Swart, 2020; Pérez and Sabelis, 2019), and complements studies which have focused on the role of individuals in co-constructing shared versions of the organisation through collective stories and narrative identities (Foroughi, 2020; Savage et al, 2018; Sörgärde, 2020).…”
Section: Discussionmentioning
confidence: 84%
“…Recent studies have examined the role of individuals as co-constructors of group and organisational identities through stories (Foroughi, 2020; Savage et al, 2018; Sörgärde, 2020) but these important contributions still focus on macro- and meso-level processes of constructing collective stories and versions of the organisation, rather than how individuals construct personal versions. Some recent studies hint at the capacity of individuals to construct their own working versions of organisational discourses and thus the nature of the organisation (Gustafsson and Swart, 2020; Pérez and Sabelis, 2019) but such processes are not their focus, and they fail to explicitly draw out and theorise them.…”
Section: Extending Narrative Identity: the Role Of A ‘Personal Social...mentioning
confidence: 99%
“…CIT has proved powerful in elucidating lived experiences of the career path. For example, Gustafsson and Swart (2020) used it by asking elite professionals to draw pictures that narrate their experience of promotion. As the authors argue, this is useful because "promotions need to be understood through the emotional experiences of individuals, whereas promotion decisions need to be viewed as situated in socio-emotional contexts" (ibid.…”
Section: Methods: Seeing the Human In Critical Hrmmentioning
confidence: 99%
“…A possible explanation for the lack of empirical research could be the relatively recent emergence of this trend and researchers have focused more on those who perceive themselves as disenfranchised (Sommerland, 2016) or as sideliners (Carroll & Vaughan, 2019). However, research has shown that even in elite professional careers, individuals can experience difficulties in adapting to new roles (Gustafsson & Swart, 2020).…”
Section: Career Transitions and Gigworking In The Legal Sectormentioning
confidence: 99%